2020
DOI: 10.1111/dme.14330
|View full text |Cite
|
Sign up to set email alerts
|

Alternative type 2 diabetes screening tests may reduce the number of U.S. adults with undiagnosed diabetes

Abstract: Aim To evaluate the U.S. population-level impact of two alternatives for initial type 2 diabetes screening [opportunistic random plasma glucose (RPG) > 6.7 mmol/l and a 1-h 50-g glucose challenge test (GCT) > 8.9 mmol/l] compared with American Diabetes Association (ADA)-recommended tests. Methods Using a sample (n = 1471) from the National Health and Nutrition Examination Survey (NHANES) 2013-2014 that represented 145 million U.S. adults at high risk for developing type 2 diabetes, we simulated a two-test scre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“… 102 Furthermore, a recent population-level modeling analysis, using the US NHANES 2013–2014 cohort, demonstrated support for the use of the GCT as part of a two-step approach, similar to that used in the diagnosis of GDM. 103 This analysis showed that a GCT followed by an OGTT or FPG identified diabetes more accurately than FPG+OGTT and HbA1c+any standard second test (FPG or 2-h PG), and that lifetime costs and quality-adjusted life-years (QALY) were comparable to those associated with the current recommended screening guidelines (requiring any two positive test results).…”
Section: The 50g Glucose Challenge Test (Gct): Screening For Dysglycementioning
confidence: 85%
“… 102 Furthermore, a recent population-level modeling analysis, using the US NHANES 2013–2014 cohort, demonstrated support for the use of the GCT as part of a two-step approach, similar to that used in the diagnosis of GDM. 103 This analysis showed that a GCT followed by an OGTT or FPG identified diabetes more accurately than FPG+OGTT and HbA1c+any standard second test (FPG or 2-h PG), and that lifetime costs and quality-adjusted life-years (QALY) were comparable to those associated with the current recommended screening guidelines (requiring any two positive test results).…”
Section: The 50g Glucose Challenge Test (Gct): Screening For Dysglycementioning
confidence: 85%
“…Thirdly, improvements in detecting and diagnosing these diseases over time could contribute to the increasing rates of combined diseases. Greater awareness and better screening practices in healthcare might be identifying more individuals living with multiple chronic conditions (26,27) .…”
Section: Discussionmentioning
confidence: 99%